Basil Bunting's Versions of Manuchehri Damghani. (November 2016) - Patton, Simon; Azadibougar, Omid
Abstract : Basil Bunting extolled the work of Manuchehri and made versions of four of Manuchehri's poems in five of his own, 1939–49. Little is known about what motivated these translations or how they relate to the Persian source texts because no detailed appraisals of them have appeared to date. A close commentary is provided here on how the content of Bunting's versions compares with that of their sources. Since it has been claimed that Bunting learned techniques from Persian poetry that helped him to refine his own style, the question is also asked what he might have learned from Manuchehri.